Prairies - O'hare Ted (Bethany Missouri Fitzgerald Books, 2008)
Easy-to-follow text teaches young readers about prairies and the different types of plants and animals that are found there.
School Library Journal, April 2008
Includes bibliographical references (p. 23) and index.
2.4
K-3
Keywords: Prairies -- Juvenile literature; Prairie ecology -- Juvenile literature; Prairies; Prairies; Readers (Elementary)